Sorption kinetic studies of medical grade activated carbon prepared from papaya seeds - Collin G. Joseph; Lee, Mei Poh (Canadian Center of Science and Education, 2008)
The aim of this investigation was to determine the adsorption behavior and kinetics of methylene blue in aqueous solution on activated carbons prepared from papaya seeds by way of the two stage activation method in self-generated atmosphere using a muffle furnace. The optimised activated carbon, AK7, had a sorption kinetic that complied with the pseudo-second order kinetics and was fitted well to Langmuir isotherm model. The highest adsorption capacity of 97.09 mg g-1was obtained when the samples (AK7) were subjected to activation temperature of 500oC for 60 minutes with the percentage of methylene blue removal efficiency of 99.5%.